Boston Keratoprosthesis: expanding the boundaries - Harissi-Dagher, Mona (Digital Journal of Ophthalmology, 2011)
The Boston Keratoprosthesis (KPro) has enjoyed good results in the adult population, particularly through its rapid clearing of the visual axis, its excellent retention rate, and the paucity of postoperative complications in recent years. Design modifications, enhanced surgical technique, and improved postoperative management have made keratoprosthesis surgery a reality in the twenty-first century and an excellent alternative for poor PK candidates.